Analisis Tingkat Kepuasan Konsumen Kedelai (Studi Kasus: Toko Irfan Jaya Kecamatan Wiradesa Kabupaten Pekalongan) - Purnomo, Brillianti Sekar Ayu; Handayani, Migie; Ekowati, Titik (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aims to analyse the level of soybean consumer satisfaction and map the relationship between the importance of a product attribute and the performance provided to consumers in the soybean business sector in Wiradesa District, Pekalongan Regency. The research location was Irfan Jaya Store, Wiradesa District, Pekalongan Regency. The research method used is a case study method, with the sample size determined using quota sampling. The sampling technique applied is accidental sampling, with respondent criteria including men and women aged 18–67 years. The analytical methods used are the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The study showed that most soybean consumers at Irfan Jaya Store are male, aged 28–37 years, with junior high school as their highest level of education. The majority of soybean consumers are traders, with an income ranging from Rp. 1,000,001 – 2,000,000, and have four to six family members. The CSI analysis results in a value of 81.63%, indicating that soybean consumers are very satisfied. The IPA analysis results show: Quadrant I: Soybean taste, freshness, colour, price at Irfan Jaya Store, and price-quality suitability. Quadrant II: Soybean availability, store location on the roadside, and accessibility of the store. Quadrant III: Soybean texture, soybean variety, price comparison between Irfan Jaya Store and other stores, and information about soybean availability. Quadrant IV: Completeness of soybean variety and waiting time for soybean availability.